Remediating Cambridge: Human and Horse Co-Relationality in a Culture of Mis-Re-Presentation - Francesca A. Brady; Jennifer McDonell (Animals)
This case study aims to problematise concepts of equine and human co-relational agency in the context of ‘mis-re-presentations’ in the Australian media of harms experienced by the Anglo Arab stallion, Cambridge, following his development of laminitis and his consequent confinement at a leading national Equestrian centre. Autoethnographic narrative is used to retrospectively and selectively narrate the evolving relationship between Cambridge and his owners, farrier, and treating veterinarians within the dominant housing and veterinary practices and welfare paradigms in equestrian culture of 1990’s Australia. Structured author/owner autoethnographic vignettes are framed by newspaper and internet reportage to highlight a productive tension between the public mediation of the case, and what it means to be fully embodied in relationship with an equine companion agent within a particular, racialised, gendered, and biopoliticised location. Adopting a phenomenologically informed intersectional feminist ethics of care perspective, a counternarrative to the gendered, racialised and essentialising rights-based judgements about Cambridge’s illness and eventual death that dominated the popular media is provided. Crucially, the autoethnographic vignettes are chosen to capture the corporeal reciprocity and rapport of forces that produced a co-created agentivity that characterised the horse’s birth, training, and treatment. The embodied interspecies knowledge that informs the training and care of equines (and all animal species) is always historically situated within permeable, dynamic worlds of self and other that are fluid, contextual, and always in relation. It is suggested that the case of Cambridge illustrates how competing stakeholder investments in animal welfare can play out in the public mediation of particular cases in ways that exclude their historical and interspecies situatedness and serve to reinforce dominant ideologies governing human and animal relationships.